2016
DOI: 10.1021/acs.orglett.6b01807
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Oxidative Nitration of α-Carbon of Carbonyls Leads to One-Pot Synthesis of Thiohydroximic Acids from Acetophenones

Abstract: A metal-free nitration of the α-C-H to carbonyl in propiophenones was achieved with I2/NaNO2 in the presence of an oxidant in dimethyl sulfoxide (DMSO) as the medium. Conversely under similar conditions, reaction of acetophenones produced thiohydroximic acids via a radical-based cascade event which involves oxidative nitration of the α-carbon to a carbonyl followed by Michael addition of the thiomethyl group from DMSO and subsequent rearrangement. Besides DMSO, the scope of the reaction encompasses other symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…We have been studying the applications of NaNO 2 and I 2 for preparing useful products in the realms of synthetic chemistry . During the course of one of our studies related to metal‐free oxidative nitration of α‐carbon to carbonyl in acetophenones with NaNO 2 /I 2 , we discovered that the reaction of 4′‐aminoacetophenone instead of producing the expected product, a thiohydroximic acid, afforded 4′‐iodoacetophenone in 62 % yield . This result suggested that 4′‐aminoacetophenone underwent nucleophilic substitution of the amino group with I 2 rather than nitration of the α‐carbon of the carbonyl group.…”
Section: Figurementioning
confidence: 93%
“…We have been studying the applications of NaNO 2 and I 2 for preparing useful products in the realms of synthetic chemistry . During the course of one of our studies related to metal‐free oxidative nitration of α‐carbon to carbonyl in acetophenones with NaNO 2 /I 2 , we discovered that the reaction of 4′‐aminoacetophenone instead of producing the expected product, a thiohydroximic acid, afforded 4′‐iodoacetophenone in 62 % yield . This result suggested that 4′‐aminoacetophenone underwent nucleophilic substitution of the amino group with I 2 rather than nitration of the α‐carbon of the carbonyl group.…”
Section: Figurementioning
confidence: 93%
“…The results show that a nitration reaction occurs along with the oxidative cyclization of 1 a , leading to the formation of non‐nitrated and nitrated products 2 a and 3 a , respectively. NaNO 2 adopts the role of a radical initiator and a nitro source ,. The treatment of 1 a with NaNO 2 (1 equiv) and K 2 S 2 O 8 (0.5 equiv) gave products 2 a and 3 a in yields of 13% and 29%, respectively (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the isomerisation reaction and with the aim of constructing a quaternary chiral centre, α‐nitroethyl ketones 2c and 2d were synthesised according to the reported procedures and then allowed to react at room temperature under solvent‐free nitro‐Mannich conditions with trifluoromethyl aldimines 1a , c , e .…”
Section: Resultsmentioning
confidence: 99%
“…Aldimines 1a , b , d , e are known compounds . Alkyl‐substituted α‐nitro ketones 2c [16a] and 2d are known compounds and were synthesised according to a literature procedure. The isolated amide is a known compound .…”
Section: Methodsmentioning
confidence: 99%